2003
DOI: 10.1081/etc-120017975
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Production Frontier and Technical Inefficiency: A Sensitivity Analysis

Abstract: The present paper focuses attention on the sensitivity of technical inefficiency to most commonly used one-sided distributions of the inefficiency error term, namely the truncated normal, the half-normal, and the exponential distributions. A generalized version of the half-normal, which does not embody the zero-mean restriction, is also explored. For each distribution, the likelihood function and the counterpart of the estimator of technical efficiency are explicitly stated (Jondrow, J., Lovell, C. A. K., Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…These parametric assumptions may lead to misspecification of rðÁÞ and invalidate any optimal derived properties of the proposed estimators (generally maximum likelihood), and consequently lead to erroneous inference. In addition, as recently pointed out by Baccouche and Kouki (2003), estimated inefficiency levels and firm efficiency rankings are sensitive to the specification of the joint density of ðY t ; X t Þ. Hence, different density specifications can lead to different conclusions regarding technology and efficiency from the same random sample.…”
Section: Introductionmentioning
confidence: 90%
“…These parametric assumptions may lead to misspecification of rðÁÞ and invalidate any optimal derived properties of the proposed estimators (generally maximum likelihood), and consequently lead to erroneous inference. In addition, as recently pointed out by Baccouche and Kouki (2003), estimated inefficiency levels and firm efficiency rankings are sensitive to the specification of the joint density of ðY t ; X t Þ. Hence, different density specifications can lead to different conclusions regarding technology and efficiency from the same random sample.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, Baccouche and Kouki [52] examined the sensitivity of SFA cost efficiency estimates to the choice of the distribution of the inefficiency error term when using a panel of firms. 4 They found that the generalized halfnormal and truncated normal provide more reliable inefficiency estimates than the exponential and the half normal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the literature has shown that measures of the inefficiencies based on models with misspecified distributions on the one-sided error u i can be misleading. For instance, Baccouche and Kouki (2003) pointed out that estimated inefficiency indices are sensitive to the most commonly used one-sided distributions of u i , but are insensitive or unaffected by the choice of the parametric functional form of the production frontier. A similar result is also found in Caudill and Ford (1993), where heteroscedasticity in the one-sided error component leads to overestimation of the intercept and underestimation of the slope and the variance of the two-sided error component in the linear parametric frontier production function.…”
Section: Introductionmentioning
confidence: 99%